STUDI EKSPERIMENTAL OUTPUT ENERGI PEMBAKARAN PADA MESO-SCALE COMBUSTOR DENGAN SUDDEN EXPANSION DAN WIRE MESH SEBAGAI FLAME HOLDER - Ryan Dwi Prasetyo (Jurusan Teknik Mesin, 2022)
Meso-combustion or combustion in the combustion chamber with a diameter of 1-10 mm is a form of fossil fuel utilization technology being developed by scientists. The development in meso-combustion is examining the use of wire mesh in the combustor section. The mesh improves heat transfer from the hot wall to the unburned gases. The size of the combustor diameter also greatly affects the flame stability area. This research was conducted by providing the main variations in the form of wiremesh use sizes 30, 60, and 90 and the combustor inlet diameter of 3,3 mm and 4,2 mm with a constant combustor outlet diameter of 4,7 mm. The results of this study indicate that the most optimal energy output and it’s efficiency is generated at the variation of inlet diameter = 3,3mm and wiremesh 90.